Detection of the types of contaminated fungi of some local and imported nuts and their ability to produce aflatoxin - Kazem, Rafead Jawad (Journal of agricultural, environmental and veterinary sciences, 2017)
This study aimed to detect the  types  of  fungi  contaminated  for  some  nuts  (seeds)  local  and  imported,  and  its  ability  to  produce  aflatoxin  in  Al-Shartah  and Al-  Rifai  districts  and  regions  of  the  two. This  study  was Accomplished  in  Shatra  General  Hospital  of  the  Health  Department  with  the  Ministry  of  Health  and  the  laboratory  of    fungi  in  the  College  of  Pharmacy  /  University  of  Dhi  Qar,  for  the  period  from  25/11/2015  until  29/03/2016,  this  study  included  collection  of    samples  of  nut  seeds  (sunflower  seeds,  walnuts  seeds,  watermelon  seeds,  Cucurbita  seeds,  Pistachio  seeds)  local  and  imported  from  vendors  in  the  restrict  of  Rifai    and  by  500  g  per  sample  of  roasted  seeds  and  stored. it  had  been  going  to  the  places  mentioned  and  collected  and  recorded  the  types  and  quantities  of  seeds  under  discussion,  were  placed  in  nylon  bags  (polyethylene)  sterile  deflated,  and  put  in  the  refrigerator  temperature  5 C °,  sample  collection  process  continues  until  the  end  of  the  probation  period. Isolated  seven  fungal  genuses  were  associated  with  the  seeds  (sunflower  seeds,  walnuts  seeds,  watermelon  seeds,  Cucurbita  seeds,  Pistachio  seeds)(imported),  which  were  intended  for  human  consumption,  as  it  was  the  highest  rate  in  the  insulation  is  the  fungus Rizhopus  spp.  (52%) followed by  Aspergillus  spp.  (17%) and  then  Rhizopus spp.  (9%) and Penicillium  spp.(6%) ,  and  finally  the  fungus  Rhizocotonia  spp.(4%)  and Mucur spp.(2%)  and  Trichderma  spp.  (1%) ,  which  was  a  relatively  low  proportion  of  isolation.
Keywords: fungi contaminated to feed; Aflatoxin; Roasted; Stored